SIMULATION OF ACID MINE DRAINAGE TREATMENT AND ADSORPTION POTENTIAL OF RARE EARTH ELEMENT (REE) USING FLY ASH ON LABORATORY SCALE - Agustian, Rido
Mining activities have the potential to form Acid Mine Drainage (AMD). The major components of AMD include SO42-, Fe2+, Mn2+, and other metal ions, including Rare Earth Elements (REEs). AMD treatment technology can be carried out by passive, active, or in situ methods. AMD treatment usually involves using various alkaline materials, one of them is fly ash, which also has the potential of REEs. Considering the potential for REEs in AMD and fly ash, this study simulates the ability of fly ash to adsorb REEs in AMD while neutralizing the AMD. This allows the acid mine drainage treatment process to be designed to maximize REE enrichment in fly ash while treating the AMD. The simulation was conducted using closed-column testing by inserting the prepared fly ash sample into the testing column. AMD was flowed into the fly ash column using a peristaltic pump. Then, the leachate and fly ash were analyzed after simulation to observe the behavior, the effectiveness and mechanism of REE adsorption as well as neutralization in AMD and the form of REE precipitation and fractionation in fly ash using IC, ICP-MS, XRD, XRF, SEM-EDS, acid digestion, and sequential extraction tests. The simulation demonstrated fly ash’s ability to neutralize AMD and adsorb REEs. The simulation produced the highest pH of 8.16, reduced the concentration of REEs by 89%, and increased the concentration of REEs, indicating that REE adsorption and enrichment had occurred in fly ash after simulation, as confirmed by XRF and EDS tests. The REE adsorption process is probably dominated by chemisorption through surface complexation, ion exchange, and precipitation mechanisms. REE fractionation in fly ash is dominated by three fractions: acid soluble, metal oxides, and aluminosilicates.